The Manifestation of Development in the Performance of the Contemporary Theatrical Actor: The Edge as an Example - Muhammad, Saad Hamid; Abdel Amir, Ahmed Mohamed (Journal of Tikrit University for Humanities, 2024)
Activism constitutes one of the paths of contemporary theatrical performance that the theatrical actor seeks to research and reach in order to develop his capabilities, abilities, and administrative skills, to renew and maintain his brilliance and prominence among the actors. Performative gestation is demonstrated by what the actor appears on stage in presenting the various characters, as he works to organize and arrange his tools. - Vocal, sensory, and motor, and exploiting his mental and muscular energies, and displaying them with high professionalism and professionalism, bringing him to the stage of brilliance, presence, and strong and lasting influence on the audience.The research included four chapters. The first chapter (the methodological framework) contained (the problem of the research, its importance, its goal, its limits, and definition of terminology), and in the second chapter the theoretical framework), the researcher divided it into two sections, the first: the concept of development divided into two axes: the first ( Development economically), the second axis is (development psychologically), and the second section deals with (the manifestation of development in the performance of the contemporary theatrical actor), reviewing the various forms and methods of performance in which the actor tries to appear, as he presents the theatrical character with proficiency and proficiency. As for the third chapter, it is devoted to the procedural framework. In the research sample, its methodology, tools, and analysis of the sample, which is the play (The Edge). The fourth chapter dealt with the results and conclusions of the research, as well as recommendations and proposals, and documented the contents and summary of the research in Arabic and English.